Women Leaders and the Church Three Crucial Questions - Belleville, Linda L. (Grand Rapids Baker Books, 2000)
This refreshingly balanced treatment compares women's roles in contemporary society and church to women??'s roles in ancient societies and the early church.
Keywords: Women clergy -- Biblical teaching. Women in church work -- Biblical teaching. Women in Christianity -- History -- Early church, ca. 30-600.